Open versus primary repair following hemorrhoidectomy for Grade III hemorrhoids: a prospective comparative study - Moghadam, Abdul Ghader Barazandeh; Mohammad, Shoaibuddin; Khan, Bushra (International Surgery Journal, 2018)
Background: The debate on open versus primary closure following haemorrhoidectomy continues to be active. Despite other methods like doppler guided haemorrhoidal artery ligation, sclerotherapy, cryotherapy, banding; open haemorrhoidectomy is performed at many places. The never-ending discussion on the better choice between open versus primary repair led to the initiation of this work. Methods: This is a prospective comparative study of a contiguous and continuous cohort of 105 cases. Alternate cases were assigned for either of the procedures. Only grade III haemorrhoids were included. Grade I and II haemorrhoids, cases treated earlier and recurrent haemorrhoids were excluded. Multiple parameters like duration of surgery, intraoperative and post-operative bleeding, pain duration and severity, time taken to return to work, use of dressings and sitz bath, wound healing time and stenosis were studied. A blinded statistical analysis was done by a third-party statistician. Results: Primary haemorrhoidectomy took a significantly longer time (P value- 0.0043). Pain was significantly less with open haemorrhoidecomy (P value- 0.0023). Post-operative pain was significant in primary repair. Pain was assessed using visual analogue scale and verbal rating scale. Open haemorrhoidectomy took a significantly longer time to heal (P value: 0.0004) and return to work (P value: 0.0001). Primary repair had stenosis requiring dilatation in a few cases. Statistical analysis was done in all cases. Conclusions: Primary repair seems to be preferred because of shorter duration of recovery despite more pain and occasional anal stenosis.